2010
DOI: 10.1021/jf101475m
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bioconversion of Polyphenols from Black Tea and Red Wine/Grape Juice by Human Intestinal Microbiota Displays Strong Interindividual Variability

Abstract: These authors equally contributed to the manuscript.Dietary polyphenols in tea and wine have been associated with beneficial health effects. After ingestion, most polyphenols are metabolized by the colonic microbiota. The current study aimed at exploring the interindividual variation of gut microbial polyphenol bioconversion from 10 healthy human subjects. In vitro fecal batch fermentations simulating conditions in the distal colon were performed using polyphenols from black tea and a mixture of red wine and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
122
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 44 publications
14
122
2
2
Order By: Relevance
“…were applied to the in vitro catabolism of black tea or a mixture of red wine and grape juice considerable variation was observed, each individual's microbiota producing a distinct catabolite profile [89]. Interestingly, all 10 microbiota were more efficient at producing 3-(3 -hydroxyphenyl) propionic acid from red wine than from black tea, whereas the yield of 3 -hydroxyphenylacetic acid was much greater from black tea than red wine.…”
Section: Controls Used In Model Fermentations Have Clearly Demonstratmentioning
confidence: 93%
See 1 more Smart Citation
“…were applied to the in vitro catabolism of black tea or a mixture of red wine and grape juice considerable variation was observed, each individual's microbiota producing a distinct catabolite profile [89]. Interestingly, all 10 microbiota were more efficient at producing 3-(3 -hydroxyphenyl) propionic acid from red wine than from black tea, whereas the yield of 3 -hydroxyphenylacetic acid was much greater from black tea than red wine.…”
Section: Controls Used In Model Fermentations Have Clearly Demonstratmentioning
confidence: 93%
“…2 and 5). Human studies in vivo and gut microbiota-fermentation studies have demonstrated that at least some of these C 6 -C 1 and possibly C 6 -C 2 phenolic acids can be decarboxylated yielding the corresponding phenols (C 6 ) or methyl-phenols (C 6 -C 1 ) [84,[86][87][88][89][90], respectively. Phloroglucinol can also be formed from chalcones and dihydrochalcones [91,92], and at least certain rumen microorganisms can reduce this to non-aromatic dihydrophloroglucinol [93,94].…”
mentioning
confidence: 99%
“…The phenolic acids consistently seen in urines from both younger and old subjects were BA, MA, 3-OHPAA, HVA, 4-OHMA, 3,4diOHPAA, HA, and 3-OHhippA with 3-OHPAA, HVA, and 3,4diOHPAA, well described rutin metabolites [27,48]. Intermediates (3,4-diOHBA, 3,4-diOHPAA, 3,4-diOHPPA) were detected in variable PAA [59] Younger Blank 3.7 (n = 6/6) 3.0-4.0 15.2 (n = 6/6) 6.0-28.1 66.1 (n = 6/6) 46.8-72.2 Raftiline 2.7 (n = 6/6) 2.9-5.2 8.6 (n = 6/6) 7.4-8.8 6.6 (n = 6/6) 6.9-10.6 Rutin 3.3 (n = 6/6) 2.3-3.9 6.0 (n = 6/6) 3.5-11.3 81.9 (n = 6/6) 44.4-95.5 Rutin + raftiline 4.3 (n = 6/6) 2.5-3. amounts at different time points, but the absence of these phenolic acids at any given point does not simply illustrate capacity, but also the kinetics in flavonol catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In older adults (40-50 years old), a higher urinary concentration of phenolic metabolites of anthocyanin such as syringic acid, p-coumaric acid, 4-hydroxybenzoic acid, and homovanillic acid was associated with higher bifidobacteria level (> 4.47 vs. < 1.18 log 10 copies per g faeces) [17]. Research into the bioavailability and metabolism of (poly)phenols, has so far been mostly limited to young adults [21][22][23][24][25][26], and inter-individual factors likely to impact on the outcome measures have rarely been studied in depth [27][28][29][30][31][32][33]. One study, in particular, looked at the effect of ageing on the absorption, metabolism, and excretion of epicatechin in healthy younger and older subjects after the consumption of cocoa flavanols, with little difference observed between subjects; the study did not, however, consider the colonic metabolism of epicatechin, or phenolic acids production [34].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…with the onset of isoxanthohumol conversion into 8-prenylnaringenin , or even hours, e.g. with the microbial conversion of tea catechins and wine polyphenols (Gross et al 2010 ).…”
Section: Read-out Of the System And How This Information Can Be Usedmentioning
confidence: 99%